The Influence of Organizational Citizenship Behavior (OCB), Work Quality and Training on Employee Performance Mediated by Teamwork in North Sumatra Province - Julian; Kiki Farida Ferrin (International Journal of Management, Economic and Accounting, 2024)
Human resources are one of the components of the organizational system, which ironically is also one of the components of the employment management system that prioritizes competition in achieving work results, both in the individual and organizational environment. Human resources (HR) are a crucial element. The results of this study are as follows: Teamwork has a positive and significant effect on Employee Performance with the original sample value of 0.531 and p values of 0.000. Work Quality had a positive and significant effect on Teamwork with the original sample value of 0.325 and p values of 0.000. The quality of work had a positive effect was insignificant with the original sample value of 0.123 and p values of 0.127. Organizational Citizenship Behavior had a positive and significant effect on Teamwork with a sample value of 0.424 and a p value of 0.000. Organizational Citizenship Behavior had a positive and significant effect on Employee Performance with an original sample value of 0.188 and p values of 0.026. The training had a positive and significant effect on Teamwork with the original sample size of 0.236 and p values of 0.021. Training had a non-significant positive effect on Employee Performance with an original sample value of 0.136 and p values of 0.077. Work Quality had a positive and significant effect on the performance of the Auditors through Teamwork with the original sample value of 0.173 and p values of 0.003. Organizational Citizenship Behavior had a positive and significant effect on the performance of the Operator through Teamwork with the original sample value of 0.225 and p values of 0.002. The training had a positive and significant effect on the performance of the Instructor through Teamwork with the original sample value of 0.125 and the p value of 0.035.